Medical thoracoscopy in evaluation of undiagnosed pleural effusion - Dar, Khurshid Ahmad; Sultan, Sheikh Tariq; Jamil, Ahmed Jamal; Mehfooz, Nazia; Shah, Naveed Nazir; Farooq, Syed Suraiya; Datta, Bikram Singh; Bhat, Firdous Manzoor; Wani, Lateef Ahmad; Bhat, Khalid Feroz (International Journal of Research in Medical Sciences, 2019)
Background: Medical thoracoscopy or pleuroscopy, in recent past has received lot of interest for diagnostic as well as therapeutic purposes. In the evaluation of undiagnosed pleural effusion, it has become a key diagnostic modality as it is a cost effective and safe procedure. The aim of present study was to assess the diagnostic yield of medical thoracoscopy in patients with undiagnosed exudative pleural effusion. Methods: This prospective study was conducted at government chest diseases hospital Srinagar between December 2016 to June 2018. One hundred and twenty-five (125) patients who fulfilled inclusion criteria were included in this study. Thoracoscopy was done using rigid thoracoscope under local anesthesia. Thoracoscopic and histopathological data of enrolled patients was collected prospectively and analysed. Results: Patients enrolled in the study were in the age range of 17 to 82 years and consisted of 80 males and 45 females. Most common thoracoscopic finding was multiple variable sized nodules (53.6%) followed by sago grain infiltration (15.2%). Malignancy was the most common histopathological diagnosis (60.8%) with metastatic adenocarcinoma being the most common histopathological diagnosis (50%). The overall diagnostic yield of thoracoscopy was 90.4%. Conclusions: Medical thoracoscopy is a safe procedure with excellent diagnostic yield for evaluation of undiagnosed pleural effusion with minimal complication rates.